2018
DOI: 10.24018/ejers.2018.3.5.750
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solidification Rates and Stress-Relief Annealing on the Mechanical Properties of Cast 6063 Aluminium Alloy

Abstract: This paper reports the influence of solidification rate and stress-relief annealing on the mechanical properties of cast 6063 Aluminium alloy (Al6063). Ingots of Al6063 were melted and then cast using sand and metal moulds. Some of the cast samples were heat treated and then cooled in natural air. Tensile test, hardness test, impact test and microstructural analysis were carried out on the samples. The results show substantial changes in the mechanical properties of the specimens. The ultimate tensile strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…These properties can be improved using mould with high thermal conductivity. Also, Stephen et al [7] and Isadare et al [9] showed the heat treatment (stress relief annealing) improved impact strength and ductility of cast aluminium alloy.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…These properties can be improved using mould with high thermal conductivity. Also, Stephen et al [7] and Isadare et al [9] showed the heat treatment (stress relief annealing) improved impact strength and ductility of cast aluminium alloy.…”
Section: Introductionmentioning
confidence: 98%
“…luminium is the most widely used non-ferrous metal for engineering applications due to its unique combination of properties; good corrosion resistance, high strength stiffness to weight ratio, good electrical and thermal conductivities, and prospects of recycling at low energy costs [1][2][3]. The properties of aluminium are normally improved by addition of alloying elements, manufacturing techniques and heat treatment [4][5][6][7][8]. Aluminium is often strenghtened by reinforcement with particles and fibres via casting (to obtain metal matrix composite) or with windings of resinimpregnated fibre strands (filaments) on its surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation